2021
DOI: 10.3390/ijerph18147272
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Survival, Place of Death, and Medical Utilization of Terminal Patients Receiving Hospital-Based and Community-Based Palliative Home Care: A Retrospective and Propensity Score Matching Cohort Study

Abstract: Evidence shows that community-based palliative home care (PHC) provision enhances continuous care and improves patient outcomes. This study compared patient survival, place of death, and medical utilization in community- versus hospital-based PHC. A retrospective cohort study was conducted of patients aged over 18 referred to either community- or hospital-based PHC from May to December 2018 at a tertiary hospital and surrounding communities in Southern Taiwan. A descriptive analysis, Chi-square test, t-test, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In terms of providing quality palliative care, patient preferences for home-based death have recently increased; however, the decision for the final place of care is occasionally affected by several unwilling factors: higher functional status, inadequately controlled symptoms, and acute reversible events [17][18][19]. With home-based palliative care, the proportion of home deaths has been reported as 52-71% [3,17]. Based on our experience with a relatively high rate of home death, we suggest that hypoxemia due to home-care-acquired infection can be treated in home-care settings, with immediate application of antibiotics and home oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of providing quality palliative care, patient preferences for home-based death have recently increased; however, the decision for the final place of care is occasionally affected by several unwilling factors: higher functional status, inadequately controlled symptoms, and acute reversible events [17][18][19]. With home-based palliative care, the proportion of home deaths has been reported as 52-71% [3,17]. Based on our experience with a relatively high rate of home death, we suggest that hypoxemia due to home-care-acquired infection can be treated in home-care settings, with immediate application of antibiotics and home oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Home-based medication, primary care, and palliative care are alternative approaches for in-hospital medication, which have been applicable for the elderly or patients with end-stage chronic diseases, including those requiring home oxygen therapy [1,2]. In comparison with in-hospital medication, home-based medication has several advantages, such as suppressing deterioration of motor and cognitive functions by avoiding hospitalization-associated disability and promoting quality of life in palliative medication [3][4][5]. Despite the growing demand for home-based medication, there remains scarce evidence of infection or respiratory failure in these settings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients who received end-of-life care in Taiwan had a life expectancy of just a few weeks or months [ 46 ]. To ensure that we could follow most of these patients until the end of their lives, we set a follow-up duration of up to 52 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…3 Some evaluations of home-based EoLC around the world have reported negative outcomes for terminally ill patients. [18][19][20][21] A study by Eagar et al 19 postulated that patients in home care experienced less improvement in physical symptoms than patients in hospital care. Another research on palliative care outcomes in Australia also revealed that terminally ill patients receiving care at home experienced poorer pain management and symptom control, than those cared for in a hospital.…”
Section: Introductionmentioning
confidence: 99%